Effect of front-surface-field and back-surface-field on the performance of GaAs based-photovoltaic cell - Gamel M.; Jern K.P.; Rashid E.; Jing L.H.; Yao L.K.; Wong B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Aluminum gallium arsenide; Conversion efficiency; Efficiency; Electronic design automation; Gallium arsenide; III-V semiconductors; Nanosensors; Nanotechnology; Photoelectrochemical cells; Photovoltaic cells; Photovoltaic effects; Semiconducting gallium; Semiconductor alloys; Active regions; Back surface fields; Band diagrams; Concentrated solar cells; Gallium arsenide cells; Illumination conditions; Silvaco; TCAD software; Solar cells